Snapshot of Cyprus Raw Goat Milk Bacterial Diversity via 16S rDNA High-Throughput Sequencing; Impact of Cold Storage Conditions - Kamilari, Eleni; Anagnostopoulos, Dimitrios A.; Papademas, Photis; Efthymiou, Maria; Tretiak, Svitlana; Tsaltas, Dimitrios (My University, 2020)
In general, it is a common practice among dairy producers to store the milk in the refrigerator directly after milking, in order to preserve it and prevent the development of spoilage microbes. However, the impact of keeping the milk in the refrigerator overnight on milk microbial diversity has been poorly investigated. This study aimed to provide a snapshot of the bacterial composition of goat milk after direct storage at −80 °C and after being kept overnight at 4 °C and then in storage at −80 °, using high-throughput sequencing (HTS). Goat milk samples from four different farms were analyzed, to reveal that milk bacterial diversity differed between the two different storage conditions. Goat milk directly stored at −80 °C was characterized by the presence of the Gram-negative contaminants Pseudomonas and Acinetobacter, in addition to the genera Corynebacterium, Chryseobacterium, Bacteroides and Clostridium. Milk samples that were kept overnight at 4 °C were characterized by a reduction in their bacterial biodiversity and the predominance of the Gram-negative, aerobic Phyllobacterium. Overall, HTS methodologies provide an in-depth identification and characterization of the goat raw milk microbiome. Further, they offer a better understanding of the contribution of cold storage conditions to milk microbiota formation. This study may assist dairy producers in improving raw milk and raw milk cheeses quality and guaranteeing consumers’ safety.
Keywords: goat milk; bacterial diversity; cold storage; high-throughput sequencing